Hydrochlorothizide-induced acute generalised exanthematous pustulosis presenting with bilateral periorbital impetigo. Issue 2 (11th February 2019) - Reap, Leo E; Rodd, Cassandra; Larios, Jose; Marshall, Michael
Abstract : Acute generalised exanthematous pustulosis (AGEP) is a severe cutaneous adverse reaction characterised by the appearance of erythematous plaques and papules with overlying non-follicular pinpoint pustules. Drugs are the cause of AGEP in approximately 90% of cases. The most common causes include anti-infective agents (aminopenicillins, quinolones, antibacterial sulfonamides and terbinafine), antimalarials and diltiazem. To the best of our knowledge, to date there has only been one report of hydrochlorothiazide-induced AGEP. There has never been a case report of losartan-induced AGEP. Here, we present a case of AGEP that is the second case purportedly caused by hydrochlorothiazide.